Removal of micropollutants and biological effects by conventional and intensified constructed wetlands treating municipal wastewater. (1st August 2021) - Sossalla, Nadine A.; Nivala, Jaime; Reemtsma, Thorsten; Schlichting, Rita; König, Maria; Forquet, Nicolas; van Afferden, Manfred; Müller, Roland A.; Escher, Beate I.
Highlights: Removal efficacy of seven treatment wetlands and a WWTP were studied for one year. Classical parameters, micropollutants and biological effects were quantified. Intensified wetlands showed highest removal of indicator chemicals and effects. Effects in outflow of intensified wetlands were mostly below effect-based triggers. Abstract: Seven treatment wetlands and a municipal wastewater treatment plant (WWTP) were weekly monitored over the course of one year for removal of conventional wastewater parameters, selected micropollutants (caffeine, ibuprofen, naproxen, benzotriazole, diclofenac, acesulfame, and carbamazepine) and biological effects. The treatment wetland designs investigated include a horizontal subsurface flow (HF) wetland and a variety of wetlands with intensification (aeration, two-stages, or reciprocating flow). Complementary to the common approach of analyzing individual chemicals, in vitro bioassays can detect the toxicity of a mixture of known and unknown components given in a water sample. A panel of five in vitro cell-based reporter gene bioassays was selected to cover environmentally relevant endpoints (AhR: indicative of activation of the aryl hydrocarbon receptor; PPARγ: binding to the peroxisome proliferator-activated receptor gamma; ERα: activation of the estrogen receptor alpha; GR: activation of the glucocorticoid receptor; oxidative stress response). While carbamazepine was persistent in the intensified treatment wetlands, mean monthly mass removal of up to 51% was achieved in the HF wetland. The two-stage wetland system showed highest removal efficacy for all biological effects (91% to >99%). The removal efficacy for biological effects ranged from 56% to 77% for the HF wetland and 60% to 99% for the WWTP. Bioanalytical equivalent concentrations (BEQs) for AhR, PPARγ, and oxidative stress response were often below the recommended effect-based trigger (EBT) values for surface water, indicating the great benefit for using nature-based solutions for water treatment. Intensified treatment wetlands remove both individual micropollutants and mixture effects more efficiently than conventional (non-aerated) HF wetlands, and in some cases, the WWTP. Graphical abstract: Image, graphical abstract